2008
DOI: 10.1002/bit.22188
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of mammalian genomic DNA using two‐phase aqueous micellar systems

Abstract: The concentration of biomarkers, such as DNA, prior to a subsequent detection step may facilitate the early detection of cancer, which could significantly increase chances for survival. In this study, the partitioning behavior of mammalian genomic DNA fragments in a two-phase aqueous micellar system was investigated using both experiment and theory. The micellar system was generated using the nonionic surfactant Triton X-114 and phosphate-buffered saline (PBS). Partition coefficients were measured under a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 44 publications
(49 reference statements)
3
31
0
1
Order By: Relevance
“…These findings are consistent with those previously obtained for samples containing DNA and 7.8 wt % Triton X-114 (which carries 9-10 EO units as its headgroup) in phosphate-buffered saline (PBS), 45 where the clear preference of DNA for the surfactant-poor phase was explained by repulsive, steric, excluded volume interactions.…”
Section: Resultssupporting
confidence: 92%
“…These findings are consistent with those previously obtained for samples containing DNA and 7.8 wt % Triton X-114 (which carries 9-10 EO units as its headgroup) in phosphate-buffered saline (PBS), 45 where the clear preference of DNA for the surfactant-poor phase was explained by repulsive, steric, excluded volume interactions.…”
Section: Resultssupporting
confidence: 92%
“…Specifically, when a volume ratio of 1:9 was used, the top phase (where the DNA wants to exist within) became 1/10 of the initial volume, and DNA became concentrated by approximately 10-fold in that phase. 29 In 2010, the Kamei group became the first to combine the technologies of ATPS and LFA. 30 Using the Triton X-114 micellar ATPS system and bacteriophage M13, they demonstrated that M13 was similarly concentrated by 10-fold into the top phase of a 1:9 volume ratio micellar ATPS.…”
Section: Concentration Of Biomoleculesmentioning
confidence: 99%
“…Gomes et al used ATPS based on PEG 600, sodium citrate and ammonium sulfate were used to partially purify pDNA from Escherichia coli alkaline lysates to overcome the drawback that the wastewater streams generated in the polymer/salt TPS have high concentrations of phosphate or ammonium ions [22]. Mashayekhi et al investigated partitioning behavior of mammalian genomic DNA fragments in TPS with micellar system which was generated using the nonionic surfactant Triton X-114 and phosphate buffered saline (PBS) [23]. The integrated process for purification of pDNA using TPS combined with other procedures such as chromatography has been also investigated [19,24,25].…”
Section: March 2011mentioning
confidence: 99%